2009
DOI: 10.3171/2008.8.jns08522
|View full text |Cite
|
Sign up to set email alerts
|

Nerve atrophy and a small cerebellopontine angle cistern in patients with trigeminal neuralgia

Abstract: Among the patients with TN, there was a statistically significant difference in the MR imaging findings of the affected side compared with the unaffected side of the trigeminal nerve. Atrophy of the trigeminal nerve and a small CPA cistern in patients with TN provides additional markers for the diagnosis of TN and helps confirm the diagnosis based on clinical examination.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
32
3
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(38 citation statements)
references
References 14 publications
2
32
3
1
Order By: Relevance
“…viduals. 4,5,7,9,10,17 In a retrospective study of 30 patients with idiopathic TN, Ha and colleagues demonstrated that, on preoperative FIESTA MRI, there was significantly more atrophy at the cisternal segment of the trigeminal nerve on the affected side than on the unaffected side compared with the affected and unaffected sides of age-and sexmatched control patients with hemifacial spasm. 5 Of note, these authors also found a significant association between the sharpness of the trigeminal-pontine angle on the affected side compared with the unaffected side, which was not found in the control group.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…viduals. 4,5,7,9,10,17 In a retrospective study of 30 patients with idiopathic TN, Ha and colleagues demonstrated that, on preoperative FIESTA MRI, there was significantly more atrophy at the cisternal segment of the trigeminal nerve on the affected side than on the unaffected side compared with the affected and unaffected sides of age-and sexmatched control patients with hemifacial spasm. 5 Of note, these authors also found a significant association between the sharpness of the trigeminal-pontine angle on the affected side compared with the unaffected side, which was not found in the control group.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have assessed the pattern of neurovascular conflict (NVC) due to crowding of the cisternal space and the neurovascular structures that occupy that space and its association with symptoms of TN. 5,7,17,18 Park and colleagues retrospectively reviewed MRI studies of 26 patients with unilateral TN treated with Gamma Knife radiosurgery. 17 They found a significantly smaller crosssectional area in the cerebellar-pontine angle cistern in the symptomatic side compared with the asymptomatic side, as well as a shorter cisternal segment of the trigeminal nerve on the affected side.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, there was a strong, statistically significant correlation between the fraction of visible trigeminal nerve (FVN) on preoperative MRI and the occurrence of a troublesome bony ridge during surgery (p<0.001) In our view, the fraction of visible trigeminal nerve describes the combination of differences in the width of the CPA cistern and the occurrence of a bony ridge of various degrees. The width of the CPA varies and is known to be narrower in patients affected with TN [20,21]. When a patient with a congenital or otherwise acquired (descending tentorium with age [21]) narrow CPA additionallyhas a bony ridge (although small, relatively speaking), the combination of the two causes problems for the surgeon.…”
Section: Preoperative Mri As a Diagnostic Toolmentioning
confidence: 98%